(untitled) - Eckstut, Samuela (Essex, UK, 1997)
Widely Read is a challenging reading skills book for intermediate students. Based on authentic text, the material is carefully designed to develop a variety of reading skills and encourage students to enjoy reading in English.
Keywords: English language,English language,Readers; Study and teaching,Textbooks for foreign speakers